NTRK and ALK rearrangements in malignant pleural mesothelioma, pulmonary neuroendocrine tumours and non-small cell lung cancer. (August 2020) - Leal, Jose Luis; Peters, Geoffrey; Szaumkessel, Marcin; Leong, Trishe; Asadi, Khashayar; Rivalland, Gareth; Do, Hongdo; Senko, Clare; Mitchell, Paul L.; Quing, Chai Zi; Dobrovic, Alexander; Thapa, Bibhusal; et al.
Highlights: NTRK and ALK gene fusions have been described in several tumor types. This includes NSCLC and atypical carcinoid, but not other thoracic malignancies. This is the first report of NTRK and ALK rearrangements in pleural mesothelioma. There is known efficacy and availability of NTRK and ALK fusion directed therapies Our data supports an agnostic screening of such fusions in this uncommon tumours. Abstract: Objectives: Gene rearrangements involving NTRK1, NTRK2, NTRK3, ROS1 and ALK have been identified in many types of cancer, including non-small cell lung cancer (NSCLC). Data in malignant pleural mesothelioma (MPM), lung neuroendocrine tumors (NETs) and small-cell lung cancer (SCLC) are lacking. Given the activity of NTRK, ROS-1 and ALK inhibitors in tumors harboring gene fusions, we sought to explore such rearrangements in these less common tumors in addition to NSCLC. Methods: Archival tumor tissue from patients with MPM, lung NETs, SCLC and NSCLC were used to create tissue microarrays. Immunohistochemistry (IHC) was performed using a cocktail of antibodies against TRK, ROS1 and ALK. IHC positive samples underwent RNA sequencing using the ArcherDX FusionPlex CTL diagnostic assay. Clinical data were obtained through retrospective chart review. Results: We performed IHC on 1116 samples: 335 MPMs, 522 NSCLCs, 105 SCLCs and 154 lung NETs. There were 23 IHC positive cases (2.1%) including eight MPMs (2.4%), eight NETs (5.2%), five SCLC (4.8%) and two NSCLC (0.4%). The following fusions were detected: one MPM with an NTRK ex10- TPM3 ex8, another MPM with an ALK ex20- EML4 ex13, one lung intermediate-grade NET (atypical carcinoid) with an ALK ex20- EML4 ex6/intron6, and two NSCLCs with an ALK ex20- EML4 ex6/intron6 rearrangement. None of the patients received targeted treatment. Conclusions: To our knowledge, we report for the first time NTRK and ALK rearrangements in a small subset of MPM. An ALK rearrangement was also detected in lung intermediate-grade NET (or atypical carcinoid). Our data suggest that IHC could be a useful screening test in such patients to ensure that all therapeutic strategies including targeted therapy are utilized.